BRAND STRATEGY FRAMEWORK FOR ISLAMIC HIGHER EDUCATION - Hasanah, Siti Ma’rifatul (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Brand is a crucial element that gives great contribution to the success of an organization, both business and nonprofit organization. Brand is an intangibles asset, but has the highest value. It is able to represent the essence of an organization, as a powerful differentiator and a tool to make decision for stakeholders. State Islamic Higher Education (Perguruan Tinggi Keagamaan Islam Negeri) as a part of the nonprofit service organization, needs to be aware to the value of branding and build a strong and sustainable brand. State Islamic College currently faces unfavorable condition, where it has many problems and society’s negative stigma. Starting from those problems, it is very urgent to conduct this research. As the focus of this study are: 1). How is the strategy in building the brand of UIN Maulana Malik Ibrahim Malang? 2). How is the strategy in brand building using PDB Triangle? 3) What is the Formulation of Brand Strategy Framework for Islamic Higher Education? This research uses a qualitative approach and case study type. Source of the data is derived from informants and documentation, which are adjusted to the research focus. The technique for data analysis uses interview, observation, and documentation. In analyzing the data, the researcher reduce and display the data then make the conclusion. For checking the data validity, source and method triangulation are also conducted. The result of this research indicates that: The strategy used by the rector to build brand is divided into two stages, (a) formulation strategy, based on QS. Al-Alaq (1-5). That includes reading and analyzing university position and making a planning strategic. (b) Implementation strategy, based on QS. Al-Muddatsir (1-7). Including the steps to develop human resources and implement the formula which made in Planning strategic. Based on the strategy that was formulated and implemented successful, including; knowledge building reconstructions, changes of status and identity university, adding the faculties and departments, build the arkan al - jami’ah , education models, and learning supporting program, corporation, developing some aspects.